THE GOOD CORPORATE GOVERNANCE AS A MEASURE TO CONTROL COMPANY EARNINGS MANAGEMENT - Dewi, Hartanti; Sahputra, Hendra; Zulfikar, Zulfikar; Dianita, Tabah (J-ISCAN: Journal of Islamic Accounting Research, 2024)
Capital Providers (Investors and Creditors) use past information to help assess the performance and prospects of a company. This performance information is contained in the financial reports presented by the company which will then influence the capital allocation carried out by the capital provider. Thus, although investment and credit decisions reflect the expectations of investors and creditors regarding the company's future performance, these expectations are generally based at least in part on evaluations of the company's past performance. Management is very aware of the trend seen by owners and external parties, namely management performance through profit proxies, thereby encouraging the emergence of earnings management. This earnings management tendency is closely related to agency theory and information asymmetry between management and owners. Various research results show that the implementation of Good Corporate Governance is a solution for many companies to overcome agency problems so that earnings management carried out by management can be controlled well. Corporate governance is one of the key elements in increasing economic efficiency, which includes a series of relationships between company management, board of directors, shareholders and other stakeholders. Corporate governance also provides a structure that facilitates determining the targets of a company, and as a means of determining performance monitoring techniques.